Suomalaiset kalevalamatriset loitsut ja niiden suullisuus Walter Ongin teorien valossa - Patrykiejew, Magdalena (Folia Scandinavica Posnaniensia, 2007)
The main goal of the paper is to describe the spells and charms of the Finnish sages as the part of the Finnish oral tradition and briefly discuss their characteristic features, such as the metre (so called Kalevala metre), alliteration and repetition on the example of one particular fragment of a spell. More attention is given to the spell as the oral phenomenon and the vocal performance it reąuired. This analysis is based on the theories of Walter Ong concerning the orality and literacy.